Effect of gender, cadence, and water immersion on ground reaction forces during stationary running - De Brito Fontana H.* (2012)
STUDY DESIGN: Controlled laboratory study. OBJECTIVES: To analyze the vertical and anteroposterior components of the ground reaction force during stationary running performed in water and on dry land, focusing on the effect of gender, level of immersion, and cadence. BACKGROUND: Stationary running, as a fundamental component of aquatic rehabilitation and training protocols, is little explored in the literature with regard to biomechanical variables, which makes it difficult to determine and control the mechanical load acting on the individuals. METHODS: Twenty-two subjects performed 1 minute of stationary running on land, immersed to the hip, and immersed to the chest at 3 different cadences:90 steps per minute, 110 steps per minute, and 130 steps per minute. Force data were acquired with a force plate, and the variables were vertical peak (Fy), loading rate (LR), anterior peak (Fx anterior), and posterior peak (Fx posterior). Data were normalized to subjects' body weight (BW) and analyzed using repeated-measures analysis of variance. RESULTS: Fy ranged from 0.98 to 2.11 BW, LR ranged from 5.38 to 11.52 BW/s, Fx anterior ranged from 0.07 to 0.14 BW, and Fx posterior ranged from 0.06 to 0.09 BW. The gender factor had no effect on the variables analyzed. A significant interaction between level of immersion and cadence was observed for Fy, Fx anterior, and Fx posterior. On dry land, Fy increased with increasing cadence, whereas in water this effect was seen only between 90 steps per minute and the 2 higher cadences. The higher the level of immersion, the lower the magnitude of Fy. LR was reduced under both water conditions and increased with increasing cadence, regardless of the level of immersion. CONCLUSION: Ground reaction forces during stationary running are similar between genders. Fy and LR are lower in water, though the values are increased at higher cadences.